Research on lemongrass oil extraction technology: hydrodistillation, steam istillation, and microwave-assisted hydrodistillation - Thien Hien, Tran; Thuong Nhan, Nguyen Phu; Thanh Ho, Van Thi; Dai Viet, Vo Nguyen; Giang Bach, Long; Duy Nguyen, Trinh (2018)
Nowaday, people's health issues are of particular interest and motivate them to focus on natural products from countless herbs and plants. Essential oil is one of the most remarkable natural substances. There are hundreds of essential oils and they contain a lot of aromatic compounds [1]. These aromatic compounds are widely used in many products in food, pharmaceuticals and cosmetics. Inside, Lemongrass (Cymbopogon citratus stapf) oil with mainly citral (neral and geranial) component has been considered an important component in the antibacterial, antifungal, antioxidant, antiseptic activities [2].